Oval window atresia with inferiorly located facial nerve: Successfully use of alternative fenestration site of cochleostomy for ossicular chain reconstruction. Issue 1 (1st January 2019) - Xie, Jing; Zhao, Peng-Fei; Wang, Wei; Gong, Shu-Sheng
Abstract: Oval window atresia is often accompanied by malpositioned facial nerve, when inferiorly located facial nerve occupies the expected site of oval window, the ossicular chain reconstruction will always be abandoned. We report the case of a 12-year-old boy with one-side middle ear deformity and hearing loss. Under surgical exploration, the tympanic segment of facial nerve occupied the entire atresia plate, we created a hole on the bony basal turn of the cochlear immediately above the round window, a hand modeled titanium stapes prosthesis was used between the handle of malleus and cochleostomy opening. The audiogram showed an average hearing improvement of 36 dBHL three months later postoperatively. For the case with oval window atresia and inferiorly located facial nerve, cochleostomy could be an effective alternative fenestration site for ossicular chain reconstruction. The prosthesis shaping is always needed for better sound conduction.